262. Assessment of occupational exposure to electromagnetic field around 1.5 T and 3.0 T MRI scanners. (December 2018) - Filice, S.; Rossi, R.; Pinardi, C.
Abstract : Purpose: MRI uses a combination of strong Static Magnetic Field ( B 0, 0 Hz), which is constantly present inside and around the MRI facility, switching gradient fields oscillating in the Very Low Frequency range (VLF, 0.3–3 KHz) and radiofrequency pulses in the Very High Frequency range (VHF, 30–300 MHz). Staff entering an MRI scanner room may experience instantaneous SMF exposure, as well as time-varying magnetic field exposure (dB/dt) at extremely low frequency, when they move through the non-uniform static magnetic field nearby the scanner. In some situations MRI staff are present inside the scanner room during image acquisition, implying the exposure to the different Electromagnetic Field (EMF). In this study we investigated the compliance of occupational exposure to MRI-related EMF with the 2013/35/EU Directive. Methods: The personnel exposure to both dB/dt and B0 during work activity were evaluated on 1.5 T and 3.0 T clinical whole body MRI scanner by using a portable electronic dosimeter for static magnetic field (Talete® Tecnorad, Italy). The dosimeters was capable of measuring B0 at 18 Hz sampling rate. The estimated values were compared with the Exposure Limit Values (ELVs) established from 2013/35/EU Directive. The electric field and magnetic field associated with VLF and VHF were measured at different positions inside the scanner room for three different acquisition technique. The measured values were compared with the Action Levels (ALs) given in 2013/35/EU Directive. For f < 100 kHz non-sinusoidal (non-monochromatic) EMF the method of weighted peak was used. Results: The ALs and the ELVs set by the 2013/35/EU Directive were not exceeded. Conclusion: The assessment of occupational exposure to electromagnetic field around 1.5 T and 3.0 T MRI scanners is difficult because of many different EMF. Furthermore many signals and modulations are present in to VHF and VLF emission spectra, besides the use into clinical practice of different equipment and acquisition techniques. In the routine daily work activities, the respect of ALs and ELVs given by 2013/35/EU Directive is demonstrated.